Analisis Dampak Perundungan Ditinjau dari Lingkungan Pergaulan Anak Usia Sekolah di SD No. 2 Kerobokan Kelod - Wijayanti, Ni Kadek Arthiwi; Suarni, Ni Ketut; Margunayasa, I Gede (MUKADIMAH: Jurnal Pendidikan, Sejarah, dan Ilmu-ilmu Sosial, 2024)
This research discusses the impact of bullying on the social environment of school-aged children with a focus on psychosocial, academic and interaction aspects in cyberspace. Delving into the dynamics of bullying, this research provides an in-depth understanding of how this phenomenon affects children's development. The method used in this research is quantitative with descriptive research type. The findings highlight the relevance of this research in the context of modern education, children's mental well-being, and the challenges of the digital world. Additionally, this research provides a foundation for the development of more effective bullying prevention and intervention strategies at the school level. By summarizing the impact of bullying on the social environment of school-age children, this research encourages collaboration between schools, parents, and the community to create an educational environment that is safe, inclusive, and supports children's positive development.